ARTUR DUCK, DE USU ET AUTHORITATE JURIS CIVILIS ROMANORUM - PODRZĘDNA ROZPRAWA CZY DZIEŁO ŚWIATOWEJ ROMANISTYKI? - Marzec, Łukasz (Zeszyty Prawnicze, 2017)
Artur Duck, De Usu et Authoritate Juris Civilis Romanorum - Mediocre or Brilliant Work? Summary De Usu et Authoritate Juris Civilis Romanorum in Dominiis Principum Christianorum, the work by Artur Duck was published in London in 1653. Duck, one o f the leading civil lawyers, a royalist, high commissioner, Master in Chancery, King’s Advocate and a chancellor of three dioceses wrote his book in exile in Oxford during the English Civil War. In his work he analysed the position and influence o f Roman Law in fourteen countries of 17th-century Europe. Apart from England, Scotland and Ireland, he researched the German Empire, France, Italy, Sicily and Naples, Poland, Hungary, Bohemia, Spain, Portugal, Denmark and Sweden. Although Duck was an Englishman, he admired Roman Law and believed it could unify and consolidate the legal systems of Christian Europe. His work shows deep knowledge of how the legal systems o f 17th-century Europe were organized and influenced by Roman Law. What seems to be of a special significance is the section of his book considering the role o f Roman law in England, where Duck was involved in judicial activity for several years as a judge and advocate. Although his work remained forgotten for centuries, contemporary science is attempting to restore it to its proper position. So far, Duck’s work has not been scientifically analysed but there is no doubt that it deserves a detailed study.